Transatlantic analysis of patient profiles and mid-term survival after isolated coronary artery bypass grafting: a head-to-head comparison between the European DuraGraft Registry and the US STS Registry - Caliskan, Etem; Misfeld, Martin; Sandner, Sigrid; Böning, Andreas; Aramendi, Jose; Salzberg, Sacha P.; Choi, Yeong-Hoon; Perrault, Louis P.; Tekin, Ilker; Cuerpo, Gregorio P.; Lopez-Menendez, Jose; Weltert, Luca P.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: In the present analysis we compare patient profiles and overall survival outcomes for up to 3 years between a European and US patient cohort undergoing isolated CABG. Methods: Patients from the European DuraGraft Registry (n=2,522) who underwent isolated CABG at 45 sites in eight European countries between 2016-2019 were compared to randomly selected patients from the STS database in the US who were operated during the same period (n=294,725). Free conduits (venous and arterial grafts) from patients in the DuraGraft registry were intra-operatively stored in DuraGraft, an endothelial damage inhibitor, before anastomosis, whereas grafts from STS registry patients in standard-of -care solutions (e.g. saline). Propensity score models (PSM) were used to account for differences in patient baseline and surgical characteristics, using a primary PSM with 35 variables (2,400patients matched) and a secondary PSM with 25 variables (2,522patients matched, sensitivity analysis). Overall survival for up to 3-years after CABG was assessed as the primary endpoint. Results: The comparison of patient profiles showed significant differences between the European and US cohort. Such differences however were well balanced after PSM for the mortality comparison. Mortality comparison at 30days, 12months and 24months between European and US patients was 2.38%vs.1.96%,4.32%vs.4.79% andv5.38%vs.6.96% respectively. At 36 months the mortality was significantly lower in the European patients when compared to their US counterparts (7.37%vs9.65%;p-value=0.016). The estimated Hazard Ratio was (HR)=1.29 (95%CI1.05-1.59). Conclusion: No significant difference in mortality was detected between groups through 2-years, but survival was significantly better in European DuraGraft registry patients at 3-years post CABG.